Informal controls in the mass media - Jankowski, Laurence; Instructional Video USA. (Lakewood, Colorado: Instructional Video USA, 2005)
Informal controls may come from various ways such as pressure from groups, consumer and advertisers. Internal controls such as organizational policy, self-criticsm,economic pressures, pressure groups and press councils also discussed.
Narrated by Dr. Laurence Jankowski.
DVD format.
Keywords: Mass media; Communication